2007
DOI: 10.1021/ja0677822
|View full text |Cite
|
Sign up to set email alerts
|

A New Anticoagulant−Antidote Pair:  Control of Thrombin Activity by Aptamers and Porphyrins

Abstract: Aptamers are nucleic acids generated by in vitro selection techniques that are able to specifically bind to ligands such as proteins. 1 A series of aptamers targeting blood clotting factors have been described that are highly effective in inhibiting blood coagulation and thus act as anticoagulants. 2 In applications, such as cardiopulmonary bypass surgery, it is crucial to reverse the anticoagulant effect. For this reason, anticoagulant/antidote effector pairs are required, and only one such pair, consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 16 publications
1
27
1
2
Order By: Relevance
“…Many research groups recently demonstrated that, among the thrombin inhibitors, the aptamers TBA 15 , TBA 29 , and a series of related modified derivatives, were effectively controllable in their anticoagulation activity adopting various methodologies, such as the use of porphyrins, of complementary oligonucleotides or of external stimuli (light or radiofrequency irradiations). In particular, on the basis of the high affinity of porphyrins for G-quadruplexes, it was shown that a small cationic porphyrin can act as an antidote for TBA 15 , reverting the anticoagulant activity of the aptamer (Joachimi et al, 2007). The same result was obtained subsequently by studying hemin, an iron-binding porphyrin which can be an efficient antidote for a modified bifunctional TBA, by efficiently replacing thrombin in the TBA-thrombin complex (Fig.…”
Section: Modulation Of Aptamers Activitymentioning
confidence: 71%
“…Many research groups recently demonstrated that, among the thrombin inhibitors, the aptamers TBA 15 , TBA 29 , and a series of related modified derivatives, were effectively controllable in their anticoagulation activity adopting various methodologies, such as the use of porphyrins, of complementary oligonucleotides or of external stimuli (light or radiofrequency irradiations). In particular, on the basis of the high affinity of porphyrins for G-quadruplexes, it was shown that a small cationic porphyrin can act as an antidote for TBA 15 , reverting the anticoagulant activity of the aptamer (Joachimi et al, 2007). The same result was obtained subsequently by studying hemin, an iron-binding porphyrin which can be an efficient antidote for a modified bifunctional TBA, by efficiently replacing thrombin in the TBA-thrombin complex (Fig.…”
Section: Modulation Of Aptamers Activitymentioning
confidence: 71%
“…[209] Das erste zu diesem Zweck eingesetzte Aptamer war ein Anti-Thrombin-GQuadruplex bildendes 15-meres Oligodesoxynucleotid. [218][219][220] Es wurden bereits klinische Studien der Phase I mit dem Aptamer, das unter dem Namen ARC183 oder HD1 während Aortokoronarer-Bypass-Operationen (CABG) einsetzbar ist, durchgeführt. Da zum Erzielen einer Wirkung jedoch die Verabreichung hoher Dosen erforderlich war, wurde die Entwicklung jedoch anschließend gestoppt.…”
Section: Aptamere Als Wirkstoffeunclassified
“…The development of anticoagulants for use in extracorporeal circuits covers a vast array of compounds, ranging from thrombin-directed aptamers [102], recombinant tick anticoagulant peptide [103,104], pentasaccharide [105,106], recombinant nematode anticoagulant [107], anti-TF antibodies [108] and active site inhibited factor VIIa [109] to recombinant tissue factor pathway inhibitors [110]. The unique conditions and local environment that define extracorporeal circuits create major challenges in pharmacotherapy application and investigation.…”
Section: Future Directionsmentioning
confidence: 99%